The Adapting Approach to Intellectual Property from a Developing Country - Robayo, Byron (Iuris Dictio, 2017)
The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) brought with it the promise to achieve the development, which never arrived. In the same way, the strategies that developing countries have adopted have not been effective enough in order to change reality. We should understand that weakening the intellectual property system is not the correct alternative, conversely a strong and balanced intellectual property system could reduce the implicit risk in the transactional cost of allocate or transfer intangible assets of intellectual property in other country, as well as encourage local innovation. The solution is much closer than we can imagine, it is inside the intellectual property system itself. However, in order to take advantage of it, it is necessary to understand all the benefits that the global system of intellectual property give us, and urgently improve the educational system to achieve the kind of technology transfer that all developing countries are seeking for.
Keywords: TRIPS; Technology Transfer; Intellectual Property; Development; Absorption Capacity